2009
DOI: 10.2337/dc08-2108
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effects of a 1-Year Dietary Intervention of a Low-Carbohydrate Diet Versus a Low-Fat Diet on Weight and Glycemic Control in Type 2 Diabetes

Abstract: OBJECTIVETo compare the effects of a 1-year intervention with a low-carbohydrate and a low-fat diet on weight loss and glycemic control in patients with type 2 diabetes.RESEARCH DESIGN AND METHODSThis study is a randomized clinical trial of 105 overweight adults with type 2 diabetes. Primary outcomes were weight and A1C. Secondary outcomes included blood pressure and lipids. Outcome measures were obtained at 3, 6, and 12 months.RESULTSThe greatest reduction in weight and A1C occurred within the first 3 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
267
7
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(295 citation statements)
references
References 24 publications
12
267
7
4
Order By: Relevance
“…The participants in the intervention group lost more weight than those in the control group at 3 and 6 months, but at 1 year, the results were not significant [39]. The faster weight loss after 3 months achieved with the very low-carb protocol, but similar results at 1 year, were confirmed later in an RCT that included 105 overweight individuals with type 2 diabetes [40]. However, the nonsustainability weight loss was no longer a limitation, after a recent meta-analysis of 13 RCTs (around half of the studies included patients with type 2 diabetes in addition to high BMI) found that very low-carb diets (<50 g carbs/d) were more effective in producing weight loss even at 1 year than low-fat diets [41].…”
Section: Step 1: Is the Patient Overweight (Bmi ≥ 25)?supporting
confidence: 67%
See 1 more Smart Citation
“…The participants in the intervention group lost more weight than those in the control group at 3 and 6 months, but at 1 year, the results were not significant [39]. The faster weight loss after 3 months achieved with the very low-carb protocol, but similar results at 1 year, were confirmed later in an RCT that included 105 overweight individuals with type 2 diabetes [40]. However, the nonsustainability weight loss was no longer a limitation, after a recent meta-analysis of 13 RCTs (around half of the studies included patients with type 2 diabetes in addition to high BMI) found that very low-carb diets (<50 g carbs/d) were more effective in producing weight loss even at 1 year than low-fat diets [41].…”
Section: Step 1: Is the Patient Overweight (Bmi ≥ 25)?supporting
confidence: 67%
“…However, a common message is that high carbohydrate intake (>50%) does not favorably affect TG and HDL in patients with diabetes. A benefit of low-carb versus low-fat diets has also been reported in other studies regarding HDL levels [40,43,48,56], TC/HDL ratio [27,56], and triglycerides [27,43,48,56].…”
Section: Step 4: Does the Patient Have A Disturbed Lipid Profile?mentioning
confidence: 57%
“…Currently, there is no ideal macronutrient distribution for all people with diabetes, according to the ADA recommendations for nutrition therapy16. For example, some studies showed better glycemic control and insulin sensitivity in patients taking lower levels of carbohydrate23, 24, 25, whereas some others showed no difference26, 27. Conflicting results were also reported by various studies regarding the clinical outcomes in patients having higher or usual protein intake28, 29, 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al demonstrated similar modest weight loss but no significant improvement in glycemic control in those with T2DM on a low fat or low carbohydrate diet after 1 year. 42 In the longest very low carbohydrate diet trial currently reported, a −0.9% reduction in HbA1c at 2 years was achieved compared with −0.5% in a Mediterranean diet and −0.4% in a low fat diet; however, the difference between groups was not significant. Only a small proportion of the study group had diabetes, limiting the power of this conclusion.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Improvement in glycemic control has not been demonstrated in other short-term studies 55 or after 1 year. 42 In the Diabetes Excess Weight Loss (DEWL) randomized controlled trial, there was no difference in glycemic control in subjects with T2DM over 2 years when the dietary intervention was implemented in a manner similar to standard clinical practice. 51 Initial changes in intake as prescribed returned to habitual consumption over time.…”
Section: Glycemic Controlmentioning
confidence: 99%